The female nude : art, obscenity, and sexuality - Nead, Lynda (London ; New York : Routledge, 1992)
Anyone who examines the history of Western art must be struck by the prevalence of images of the female body. More than any other subject, the female nude connotes `art'. The framed image of a female body, hung on the walls of an art gallery, is an icon of Western culture, a symbol of civilization and accomplishment. But how and why did the female nude acquire this status? The Female Nude brings together, in an entirely new way, analysis of the historical tradition of the female nude and discussion of recent feminist art, and by exploring the ways in which acceptable and unacceptable images of the female body are produced and maintained, renews recent debates on high culture and pornography. The Female Nude represents the first feminist survey of the most significant subject in Western art. It reveals how the female nude is now both at the centre and at the margins of high culture. At the centre, and within art historical discourse, the female nude is seen as the visual culmination of enlightenment aesthetics; at the edge, it risks losing its repectability and spilling over into the obscene.
Introduction -- Part I. Theorizing The Female Nude -- Chapter 1. Framing The Female Body -- Chapter 2. A Discourse on the Naked and the Nude -- Chapter 3. A Study of Ideal Art -- Chapter 4. Aesthetics and the Female Nude -- Chapter 5. Obscenity and the Sublime -- Part II. Redrawing the Lines -- Chapter 1. 'The Damaged Venus' -- Chapter 2. The Framework of Tradition -- Chapter 3. The Lessons of the Life Class -- Chapter 4. Art Criticism and Sexual Metaphor -- Chapter 5. Breaking Open the Boundaries -- Chapter 6. Redrawing the Lines -- Part III. Cultural Distinctions -- Chapter 1. Sacred Frontiers -- c Chapter 2. Pure and Motivated Pleasure -- Chapter 3. Policing the Boundaries -- Chapter 4. Displaying the Female Body -- Chapter 5. Erotic Art: A Frame for Desire.
Includes bibliographical references (pages 122-130) and index.
Print version record.
eBooks on EBSCOhost
Keywords: Female nude in art; Sex in art; Nude in art; Women in art; Anatomy, Artistic; Anatomy, Artistic; Nu; Femmes dans l'art.; Sexualité dans l'art.; Nu féminin.; Anatomie artistique; nudes (representations); ART -- Subjects & Themes -- Portraits; ART -- Subjects & Themes -- Human Figure; Women in art; Nude in art; Female nude in art; Sex in art; Visual arts -- Special subjects -- Women -- Nudes